P3.246 Prevalence of STI/HIV and Assessment of Risky Behaviours Among Sex Workers. (13th July 2013) - Asmaryan, A; Papoyan, A; Hakobyan, A; Grigoryan, T; Hovhannisyan, R; Petrosyan, Z; Balayan, T
Abstract : Background: HIV biological and behavioural surveillance has been conducted repeatedly in Armenia starting from the year of 2002. The most recent STI/HIV integrated biological and behavioural surveillance (IBBS) was conducted in Armenia in 2012. Populations for conducting the surveillance were defined depending on the epidemiological situation, and current data on HIV prevalence in different populations. Sex workers (SWs) were involved in this surveillance. Methods: IBBS among SWs was conducted in three biggest cities of Armenia, respondent driven sampling (RDS) was used. The sample size in Yerevan, capital was 300 with mean age of 35.5. Results: HIV prevalence among SWs in Yerevan was 1.3%, syphilis - 4.3%, trichomoniasis - 22.5%, gonorrhoea - 6.6%. The indicator of knowledge about HIV prevention was 35.4% (34% in 2010). Condom use with non-commercial partners was low. Only 40% of SWs (30.1% in 2010) used condoms at last sex with non-commercial partners, and 27.4% (30.8% in 2010) used condoms consistently. 90% of SWs (92.9% in 2010) used condoms at last sex with clients and 80% (88.5% in 2010) used condoms consistently. 67.8% of SWs had sex with non-commercial partners in the past 1 year. On average, one SW has 4.8 clients per week, 18 clients per month. The percentage of SWs tested for HIV in the past 12 months was only 37.5%. Percentage of SWs exposed to HIV prevention programmes made 49.2%. Conclusion: Condom use with non-commercial partners was rather low among SWs, which creates a risk of further spread of HIV infection not only within this group, but also outside it. Though HIV prevalence among SWs was comparatively low, STI prevalence among them was high, which proves their risky behaviour. As appears from the above, the services on HIV prevention and STI management for SWs should be expanded and optimised.